The Effect of Leadership and Work Environment on the Performance of Malang Souvenir MSMEs through Work Motivation and Job Satisfaction - Prastiono, Suryo; Sudarmiatin; Heri Pratikto (International journal of technology and education research, 2026)
This study aims to examine and analyze the influence of leadership and work environment—mediated by work motivation and job satisfaction—on the performance of souvenir-selling MSMEs in Malang City. The growth of SMEs in Malang City has experienced rapid growth due to the boost from the tourism sector, which in turn requires business owners to have increasingly better organizational performance to face the level of competition. However, the performance of SMEs is often hampered by internal problems closely related to human resource management. The primary issues frequently observed in the field include suboptimal leadership and work environments that fail to meet standards of comfort or work orderliness. Using a quantitative approach, this study evaluates various hypotheses covering both the direct and indirect effects of these variables. Specifically, this study provides an in-depth analysis of the roles of work motivation and job satisfaction as mediating variables in the relationship between leadership and work environment on SME performance. It is hoped that the results of this study will provide empirical evidence as well as strategic recommendations useful for the development and improvement of SME performance in Malang City.